Climate Variability and Water Mass Formation in the Eastern Mediterranean Sea - Sofianos, S.; Vervatis, V.; Skliris, N.; Somot, S.; Lascaratos, A.; Mantziafou, A. (Advances in Meteorology, Climatology and Atmospheric Physics, 2013)
Recent changes of the thermohaline circulation in the Eastern Mediterranean (i.e. the Eastern Mediterranean Transient) and older observations of the thermohaline structure of the Aegean-Levantine region (with events of dramatic changes of deep water characteristics) reveal the very sensitive character of the regional thermohaline circulation pattern. This and the long term variability of seawater characteristics in various Mediterranean basins show that the deep water mass formation processes in the region can be greatly affected by climate variability and the characteristics of the extreme atmospheric forcing events. Theoretical work and modeling experiments point out the effectiveness of extreme events and periods of abnormal atmospheric conditions to produce deep waters of different characteristics and different equilibrium depth. Studying the mechanisms involved in the air-sea interaction under extreme event conditions, with available observations and modeling techniques, and monitoring important sites of water mass formation becomes very important for understanding the regional dynamics of the water cycle and their effect on the climate of the whole Mediterranean Sea region.